The determining factors of productivity and competitiveness from the perspective of territorial and sustainable development - Flores-Tapia, Carlos Ernesto; Pérez-González, María del Carmen; Maza-Ávila, Francisco Javier; Flores-Cevallos, Karla Lissette (Iberoamerican Journal of Development Studies, 2022)
In the present research work, it is identified the determining factors of productivity and the competitiveness in the province of Tungurahua (Ecuador) from the territorial and sustainable development perspective, through the use of three techniques: the individualized interview, the focus group and the survey of the different representative territorial actors, coming to the conclusion, in this case, that the driving factors are: the human capacities, the politic and economic environment, the financial capital, the business capital, the natural capital, the technology capital, the institutional capital, the social capital, and the infrastructure capital. This study contributes with information and results that can be used as input in the elaboration of public policies, aimed to promote the provincial productivity and competitiveness.
Keywords: development; economics; productivity; competitiveness; qualitative methods; Ecuador